Renal Artery Stenosis Precipitates Hyponatremic Hypertensive Syndrome and Posterior Reversible Leukoencephalopathy - Parikh, Pranav; Duhame, Danielle; Monahan, Laura; Woroniecki, Robert (Frontiers in Pediatrics, 2015)
Background: Hyponatremic hypertensive syndrome (HHS) is an uncommon disorder usually encountered in the adult population with unilateral renal artery stenosis and is under-recognized in the pediatric population. Case Diagnosis/ Treatment: A 19-month-old male presented with new-onset status epilepticus associated with neurological sequelae, and hypertension to a high of 248/150 mmHg. Lab work revealed significant hyponatremia, elevated peripheral renin activity, and increase in aldosterone and ADH levels. A diagnosis of hyponatremic-hypertensive syndrome (HHS) was made. Initial analysis revealed a high-grade proximal renal artery stenosis by MRI and angiogram. EEG and an MRI of the brain demonstrated characteristic abnormalities of the left temporal-parietal regions consistent with posterior reversible leukoencephalopathy syndrome (PRES). The patient responded to right renal artery balloon dilation and stent placement. Since intervention and close blood pressure control with Amlodipine, the patient has been free of seizures and is neurologically intact. Conclusions: We report a case of malignant hypertension in a 19 month old male secondary to renal artery stenosis with associated HHS and PRES. Prognosis of PRES in children with renal disease is excellent. Prompt intervention may offer near complete resolution of physiologic and symptomatic effects of HHS and PRES due to high-grade renal artery stenosis. This report was written with parental consent for de-identified case presentation and radiographs for the educational benefit of other medical professionals.